Modulating retinoid-X-receptor alpha (RXRA) expression sensitizes chronic myeloid leukemia cells to imatinib in vitro and reduces disease burden in vivo - Rajamani, Bharathi M.; Illangeswaran, Raveen Stephen Stallon; Benjamin, Esther Sathya Bama; Balakrishnan, Balaji; Jebanesan, Daniel Zechariah Paul; Das, Saswati; Pai, Aswin Anand; Vidhyadharan, Rakhi Thalayattu; Mohan, Ajith; Karathedath, Sreeja; Abraham, Aby; Mathews, Vikram; et al. (Frontiers in Pharmacology, 2023)
The ligand-activated transcription factors, nuclear hormone receptors (NHRs), remain unexplored in hematological malignancies except for retinoic acid receptor α (RARA). Here we profiled the expression of various NHRs and their coregulators in CML cell lines and identified a significant differential expression pattern between inherently imatinib (IM)-sensitive and resistant cell lines. RXRA was downregulated in CML cell lines inherently resistant to IM and in primary CML CD34+ cells. Pre-treatment with clinically relevant RXRA ligands improved sensitivity to IM in-vitro in both CML cell lines and primary CML cells. This combination effectively reduced the viability and colony-forming capacity of CML CD34+ cells in-vitro. In-vivo, this combination reduced leukemic burden and prolonged survival. Overexpression (OE) of RXRA inhibited proliferation and improved sensitivity to IM in-vitro. In-vivo, RXRA OE cells showed reduced engraftment of cells in the bone marrow, improved sensitivity to IM, and prolonged survival. Both RXRA OE and ligand treatment markedly reduced BCR::ABL1 downstream kinase activation, activating apoptotic cascades and improving sensitivity to IM. Importantly, RXRA OE also led to the disruption of the oxidative capacity of these cells. Combining IM with clinically available RXRA ligands could form an alternative treatment strategy in CML patients with suboptimal response to IM.